An exploratory study into the unmet supportive needs of breast cancer patients. (5th June 2013) - McGarry, S.; Ward, C.; Garrod, R.; Marsden, J.
<x xml:space="preserve">Abstract</x> This study explores the unmet supportive needs of people with breast cancer attending a London NHS Foundation Trust Hospital. A mixed methods approach was used. One hundred and one patients completed a specially designed questionnaire focusing on their concerns in the previous week, and whether they felt they had been offered sufficient support from health professionals. Seven semi‐structured interviews were then completed in order to gain insight into the need for future developments of services for patients with breast cancer. Pearson's chi‐squared analysis was used to examine whether symptoms reported within 1 year of diagnosis differed from symptoms reported more than 1 year post diagnosis. Fatigue was the most common concern expressed (53%) with no significant difference between the two groups. Emotional concerns and pain were also highly reported (35% and 36%). Only 32% of the questionnaire participants reported that they had been offered support in dealing with their concerns. Most participants (65%) would have liked more support from the healthcare team. From the interviews it was clear that whilst there are gaps in services available, participants were not aware of the range of services already available for people with breast cancer. The results of this study have helped to inform service development, particularly around the management of fatigue.